STRATEGI PENGEMBANGAN INDUSTRI PRODUK HALAL - Yulia, Lady (Direktorat Jenderal Bimbingan Masyarakat Islam, 2015)
Abstract In the era of globalization, business of halal products has been a major contributing sectors on the world economy. Sector of halal products has been into areas that dominate global trade business. With the huge market potential, in which the Muslim world today has exceeded 1.6 billion, also supported by development of halal lifestyle of non-Muslim communities, it leading to the potential market for halal products is increasing. In this case, halal products have become rahmatan lil Alamin for that use or consume it or for those who are involved in the business of halal products. In addition to halal products provide benefit for those who consume it, also provide economic value to businesses halal products. Indonesia with the largest Muslim community, may take a dominant role in the global halal products business. In order for domestic halal industry can grow and develop rapidly so as to offset the global halal products trade, it is necessary to work hard to encourage the rise of Indonesian halal industry. Industrial products are acceptable and desirable community itself and become a mainstay of export commodities so as to move the real sector and the national economy it is necessary to foster a proper strategy for the development of halal industry in Indonesia.   Abstraksi Pada era globalisasi, bisnis produk halal tidak dipungkiri lagi telah menjadi  sektor yang berkontribusi besar pada perekonomian dunia. Sektor produk halal menjadi bidang yang mendominasi bisnis perdagangan global. Dengan potensi pasar sangat besar, dimana muslim dunia saat ini sudah  melebihi 1,6 miliar, juga didukung dengan berkembanganya gaya hidup halal masyarakat non-muslim, menyebabkan potensi pasar produk halal semakin meningkat. Dalam hal ini, produk halal telah menjadi rahmatan lil alamîn bagi yang menggunakan atau yang mengonsumsinya atau bagi yang terlibat dalam bisnis produk halal. Selain produk halal memberikan kebaikan bagi yang mengonsumsinya, juga memberikan nilai ekonomi bagi pelaku bisnis produk halal. Indonesia dengan jumlah masyarakat muslim terbesar, berpeluang dominan mengambil peran dalam bisnis produk halal global. Agar industri produk  halal dalam negeri dapat tumbuh dan berkembang pesat sehingga mampu mengimbangi perdagangan produk halal global, maka perlu kerja keras mendorong bangkitnya industri produk halal Indonesia. Produk industri yang dapat diterima dan diminati masyarakat sendiri dan menjadi andalan komoditi ekspor sehingga mampu menggerakkan sektor riil dan menumbuhkan perekonomian nasional maka perlu strategi yang tepat untuk pengembangan industri produk halal Indonesia.